A fuzzy logic based assessment algorithm for developing a warehouse assessment scheme. (June 2022) - AlAlawin, Abdallah H.; AlAlaween, Wafa' H.; Salem, Mujahed A.; Mahfouf, Mahdi; Albashabsheh, Nibal T.; He, Changjiang
Highlights: A Fuzzy Logic Based Assessment Algorithm is proposed. A warehouse assessment scheme is developed based on A Fuzzy Logic Based Assessment algorithm. Various warehouses are successfully assessed. Abstract: A new integrated assessment algorithm is proposed for a warehouse assessment scheme. This new algorithm integrates three paradigms, namely, Grey Relational Analysis (GRA), Data Envelopment Analysis (DEA), and an Interval Type-2 Fuzzy Logic System (IT2FLS). Based on the defined criteria and the various warehouses assessed according to these criteria, the GRA is employed to determine the grey relational grade. The DEA is, then, utilized to estimate the warehouse efficiency scores. Finally, the IT2FLS is developed to map the efficiency scores of the warehouses to the assessed values of the defined criteria. The developed IT2FLS can be used to assess new warehouses without re-performing the calculations of the GRA and the DEA. Validated on several warehouses, the integrated assessment algorithm can assess warehouses successfully, and can tackle the uncertainties during the assessment process. In addition to comparing the warehouses with the best practice, it can also provide managers with a linguistic understanding of the effect of the defined criteria on the warehouse performance.